2012
DOI: 10.1021/es204087q
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Pd-Based Catalytic Treatment of Priority Contaminants in Water

Abstract: Catalytic reduction of water contaminants using palladium (Pd)-based catalysts and hydrogen gas as a reductant has been extensively studied at the bench-scale, but due to technical challenges it has only been limitedly applied at the field-scale. To motivate research that can overcome these technical challenges, this review critically analyzes the published research in the area of Pd-based catalytic reduction of priority drinking water contaminants (i.e., halogenated organics, oxyanions, and nitrosamines), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
327
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(336 citation statements)
references
References 200 publications
9
327
0
Order By: Relevance
“…Palladium catalysts have been proven to have the unique property of activating H 2 and catalyzing the electrochemical reduction of H + or H 2 O to produce adsorbed atomic H*, which is a much stronger reducing agent than H 2 in catalytic reduction reactions [16]. Some studies found that coupling two metals with different oxidizing abilities could enhance the generation of electrons [17], and some chemical reactions were reported to show better activity and selectivity when using bimetallic and trimetallic catalysts compared with monometallic Pd catalysts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Palladium catalysts have been proven to have the unique property of activating H 2 and catalyzing the electrochemical reduction of H + or H 2 O to produce adsorbed atomic H*, which is a much stronger reducing agent than H 2 in catalytic reduction reactions [16]. Some studies found that coupling two metals with different oxidizing abilities could enhance the generation of electrons [17], and some chemical reactions were reported to show better activity and selectivity when using bimetallic and trimetallic catalysts compared with monometallic Pd catalysts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Expectedly, a significant inhibition of NFZ reduction was observed at the Pd-Ni foam in the presence of t-BuOH (Figure 4c). Pd is well-known to have the unique property of activating protons to atomic H* and subsequently adsorbing atomic H* [48,49]. Therefore, the reduction of NFZ at the Pd-Ni foam mainly proceeded via H* mediation.…”
Section: Scheme 1 Transformation Pathway Of Degradation Productsmentioning
confidence: 99%
“…Palladium (Pd)-based catalysis has been considered as a promising water treatment strategy, as Pd has exceptional capability in providing atomic H and can catalyze the reductive transformation of a number of priority contaminants (e.g., chlorinated compounds, oxyanions and aromatics) (Hosseinkhani et al, 2013;And and Reinhard, 1999;Chaplin et al, 2012;Cortese and Heck, 1977;Davie et al, 2006). A variety of chemical and physical procedures could be used for the synthesis of Pd nanoparticles.…”
Section: Introductionmentioning
confidence: 99%